2014
DOI: 10.1039/c4ay01885k
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive surface-enhanced Raman scattering detection of alkaline phosphatase

Abstract: In this study, an ultrasensitive surface-enhanced Raman scattering (SERS) detection of alkaline phosphatase (ALP) has been developed, in which nile blue A (NBA) was chosen to replace nitro blue tetrazolium chloride (NBT) in a reactive system of 5-bromo-4-chloro-3-indolyl phosphate (BCIP), NBT, and ALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 17 publications
(15 reference statements)
0
15
0
1
Order By: Relevance
“…Nile blue A is Raman active and they used it to replace nitro blue tetrazolium that is more commonly used. The oxidized form is Raman active and it can be reduced by the ALP substrate product effectively turning off signal …”
Section: Applications Of Nile Red and Nile Bluementioning
confidence: 99%
“…Nile blue A is Raman active and they used it to replace nitro blue tetrazolium that is more commonly used. The oxidized form is Raman active and it can be reduced by the ALP substrate product effectively turning off signal …”
Section: Applications Of Nile Red and Nile Bluementioning
confidence: 99%
“…It was displayed in Figure 2(i) that the Raman spectra of the NBA, NBA-labeled AgNWs, and NBA-labeled AgNW@ AuNPs were employed to explore the SERS effect of the AgNW@AuNPs. e aromatic ring vibrations resulted in the characteristic peak of NBA at 592 cm −1 [34]. Compared to the slight variation of the SERS signal of the 0.1 M NBA, the SERS signal of the NBA-labeled AgNW was lower than that of the NBA-labeled AgNW@AuNPs, which indicated that the AgNW@AuNPs could enhance the Raman signal intensity better.…”
Section: Characterization Of Ag Nanowires and Agnw@aunpsmentioning
confidence: 92%
“…The use of nanoparticles simultaneously with enzymes allowed for combining the functions of the carrier of active components of immunoassay (antibodies, antigens) and the enzymatic transformation of substrates [ 168 ]. The substrate of alkaline phosphatase, the so-called 5-bromo-4-chloro-3-indolyl phosphate (BCIP), in the immunoassay is hydrolyzed to the inorganic phosphate and sole active compound 5-bromo-4-chloro-3-indole (BCI) [ 169 , 170 ]. The resulting product of the reaction has characteristic bands detected during the SERS immunoassay.…”
Section: Recent Advances Of Raman Spectroscopy In Biosensingmentioning
confidence: 99%